FACTORS THAT AFFECT THE IN VITRO MULTIPLICATION OF BLUEBERRY TREES - Erig, Alan Cristiano; Schurch, Márcia Wulff (Scientia Agraria, 2006)
The objective of this work was to determine the cytokinin type, the light quality and the explant orientation in the culture medium that favor the in vitro multiplication of blueberry shoots cv. Delite. In the first experiment, the treatments applied were two cytokinins in the culture medium (2iP [25 M] and zeatin [18 µM]) and two light qualities (white and green). In the second experiment, the treatments were constituted of two cytokinins used in the culture medium (2iP [25 µM] and zeatin [18 µM]) and two explants orientations in the culture medium (vertical and horizontal). In both experiments the completely randomized experimental design was used, in factorial outline 2 x 2. The basal culture medium, used in the two experiments, was constituted by the WPM salts and the MS vitamins, added of myo-inositol (100 mg.L-1), sucrose (30 g.L-1) and agar (6 g.L-1). To the 30 days in culture it were evaluated the mean number of shoots and buds for explant, the mean length of the shoots and the length of the shoot more developed (major). In the second experiment it was also determined the multiplication rate. It was observed that the in vitro multiplication of blueberry shoots cv. Delite is favored with the cultivation of the explants in culture medium with zeatin (18 µM) and under white light. The explants cultivated in the horizontal orientation in the culture medium had larger mean number of shoots.